Kampania wyborcza i jej przebieg w wyborach samorządowych 2006 r. w Koninie i powiecie konińskim (Świat Idei i Polityki, 2007)
The article presents the course and character of the political electoral rivalry conducted during the selfgovernment campaign in 2006 in Konin town and Konin Poviat. The starting point for the analysis and the electoral fight waged by the campaign participants was the domination of the Democratic Left Alliance (SLD) in wielding power in the town since 1992. It focused on the following program issues: construction investments in the town and the region, and from the side of the opposition - the fight for decommunization of the town office. Observers of the local political stage agreed that the results of the discussed selfgovernment elections depended on the new electoral regulations based on blocking electoral registers. In Konin, three election blocs were established, and 5 people ran for mayor. The further part of the text presents the election results, in which the result of achieved electoral attendance proved to be particularly important as it attested to the strengthening of democratic standards and customs. The winner of the selfgovernment elections in Konin was the Civic Platform (PO), whereas further fight for mayor was waged by a politician of SLD and a woman candidate from PO. However, the negative campaign conducted by the latter before the second round of the elections was not accepted by Konin residents, who opted for keeping the leftwing government in the town.